Economic value for traits of breeding objective of crossbred chickens under different production systems - Khan, Md. Kabirul Islam; Momin, Md. Moksedul; Khatun, Jannatara; Khan, Md. Mashiur Rahman (Journal of Tropical Agriculture, 2024)
A linear, deterministic model was used to calculate the annual profit of a hen and economic value for important traits of Hilly and Fayoumi (Fay) crossbred chickens under intensive and semi-intensive production systems in consideration of output and input variables. The economic value of different traits was calculated after re-running the model with changes of one unit of each trait value and holding other trait value as constant. Results showed that the sale of growers and culled breeding stock has impacted the revenues. Surplus growers (cockerel and pullet) accounted for 75 to 78% of the total revenues. The higher revenue was obtained from Hilly × Fay (F1 ) in intensive production system and the lowest for Hilly × F1 generation in other system. Feed costs account for 80 to 86% of the total production costs. The annual profit of a hen varied from USD 4.97 to 11.78. The economic values of egg production, fertility, hatchability and live weight were positive, however, negative values were obtained for age at sexual maturity of males and feed intake. The positive economic values of traits lead the higher profitability. Changes in the base price of egg, live weight and feed cost ±10% found the profitability and economic values were fluctuated.